Peran Shepherd Leadership Guru Kristen Terhadap Pemuridan Generasi Z di SMA XYZ di Tangerang Selatan [The Role of Christian Teachers as Shepherd Leaders in Discipling the Z Generation of XYZ High School in South Tangerang] - Ngatmiati Ngatmiati; Hendra Tjahyadi (Universitas Pelita Harapan, 2022)
Generation Z in Indonesia is a demographic bonus that has an essential role in the future. They need to be prepared to face various challenges with strong faith and character. KTB (Growing Together Group) is an effective means to grow one’s spirituality and character. The role of the KTB leader as a shepherd leader is crucial in providing guidance, leadership, and exemplary in good relationships. This study aims to identify the important role of shepherd leadership for Christian teachers in effective discipleship for Generation Z at XYZ Senior High School in South Tangerang and demonstrates the significant impact of shepherd leadership on Christian teachers who make disciples of Generation Z. This study uses a case study model with a qualitative approach. Research subjects were conducted on 8 KTB leaders and 3 KTB members. The instruments used were interviews, FGDs, and document studies. This study indicates that the role of shepherd leadership for Christian teachers has a significant impact on the disciple mentorship of Generation Z to help them have strong faith in Christ, grow in character, and impact others through the talents that God has given.